2008
DOI: 10.4028/www.scientific.net/ddf.277.177
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion during Powder Metallurgy Synthesis of Titanium Alloys

Abstract: In the present study titanium alloys were synthesized by the blended elemental press-andsinter powder metallurgy approach using hydrogenated titanium powder. Experimental investigation and modeling of the homogenization processes during synthesis were used to analyze peculiarities of mass transfer and factors affecting diffusion. Processes of alloying elements redistribution during chemical homogenization of powder blends are shown to be strongly dependent on the chemical composition of the initial powders. Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 4 publications
1
42
0
2
Order By: Relevance
“…The obtained sintered density was close to ~99 % by using Ti powders containing 3 wt. % hydrogen [19]. This is considered to be the lowest cost powder metallurgy technique.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained sintered density was close to ~99 % by using Ti powders containing 3 wt. % hydrogen [19]. This is considered to be the lowest cost powder metallurgy technique.…”
Section: Introductionmentioning
confidence: 99%
“…Una posible explicación es el aumento de la reacción del titanio con la bandeja soporte así como el aumento de la difusión del oxí-geno en borde de grano. El efecto del oxígeno es más perjudicial en las aleaciones alfa más beta que en el titanio puro, por la mayor cantidad de bordes de grano generados durante la difusión del elemento betá-geno [6] . En cuanto a las interacciones cruzadas de varios factores, los valores negativos indican un efecto combinado perjudicial al combinar ambos factores.…”
Section: Influencia De Los Parámetros Del Procesado Sobre La Respuestunclassified
“…No obstante, la utilización de una temperatura más baja limita la difusión en estado sólido y puede ser un inconveniente importante para este tipo de aleaciones beta [4][5][6] .…”
Section: Introductionunclassified
“…Since 2000, a significant amount of work regarding vacuum sintering of hydrogenated Ti powder has been reported by Ivasishin et al [147,170,175,[192][193][194][195][196] and Savvakin et al [197] It has been reported that a blend of Ti hydride with 10 wt-% 60Al/40V master-alloy powder produced Ti-6Al-4V with 98.5-99.5% TD in the as-sintered state, versus 90-95% when metallic Ti powder was used [193]. Additionally, it has been reported that using Ti hydride produced samples with an as-sintered oxygen content of 0.21 versus 0.39 wt-% when metallic Ti powder was used [198].…”
Section: Vacuum Sintering Tihmentioning
confidence: 99%